1985
DOI: 10.1111/j.1474-8673.1985.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECTS OF AMOSULALOL, a NOVEL COMBINED Α‐ AND Β‐ADRENORECEPTOR ANTAGONIST, ON THE RAT ISOLATED RIGHT VENTRICLE AND AORTA

Abstract: The effect of amosulalol on the accumulation of radioactivity from [3H]-noradrenaline and on the subsequent spontaneous and nerve stimulation-evoked outflow of radioactivity have been investigated in the rat isolated right ventricle. In addition the effect of amosulalol on the contractions of the electrically-driven directly muscle stimulated rat right ventricle to isoprenaline and of the rat isolated aorta to phenylephrine and 5-hydroxytryptamine are reported. Amosulalol at 10(-6)M did not prevent the accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that non-cumulative 5-HT addition to the rat aorta produces initial fast and secondary slow contractile responses (Hughes & Doggrell, 1985;Nakaki, Roth, Chuang & Costa, 1985;Doggrell, 1987). The present study demonstrates that immediate fast and secondary slow responses of the rat aorta are also obtained on cumulative 5-HT addition.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that non-cumulative 5-HT addition to the rat aorta produces initial fast and secondary slow contractile responses (Hughes & Doggrell, 1985;Nakaki, Roth, Chuang & Costa, 1985;Doggrell, 1987). The present study demonstrates that immediate fast and secondary slow responses of the rat aorta are also obtained on cumulative 5-HT addition.…”
Section: Discussionmentioning
confidence: 98%
“…It was not unexpected that ( f )-, ( + )-, and (-)-amosulalol caused membrane stabilizing activity on the rat left atria as we have previously demonstrated membrane stabilizing activity with these drugs on the rat right ventricle. 11,14 The mechanism underlying membrane stabilizing activity with P-blockers on the heart is poorly defined. The concentration of ( f )-amosulalol and ( f )-propranolol that causes membrane-stabilizing activity is dependent on the cardiac tissue studied.…”
Section: Discussionmentioning
confidence: 99%